The Influencing Factors of Participation in Online Timebank Nursing for Community Elderly in Beijing, China - Yan Wu; Yanran Ding; Cong Hu; Lei Wang (Frontiers Media S.A., 2021)
This study uses the logit model through questionnaire data of Beijing in 2019 to investigate the participation willingness of online timebank elderly care, especially to discover different influencing factors on the participation willingness between the youth group and the elderly group. We find that: First, the health status of elderly people and the number of elder families of young people have significant positive impacts on their willingness to participate in online timebank. Second, the experience of participating in voluntary activities has a significant positive effect and it has a far greater impact in the young group than that in the elderly group. Third, the more the free time, the higher the participation willingness in the young group, but it is the opposite in the elderly group. Fourth, the years of education and party member have significant promoting effects on the participation willingness in both groups. Such heterogeneous influencing factors can help develop online timebank nursing for dealing with the increasingly serious population aging problem in China and also other developing countries.